Scientific Platform abstracts - Iannacone, Jose (2020)
IX Congress of the Society of Environmental Toxicology and Chemistry (SETAC LA) and the II Peruvian Congress of Ecotoxicology and Environmental Chemistry (SETAC PERU)– International Meeting “Ecotoxicology and Social Responsibility"